The Genetic Resources Policy Initiative Newsletter: December 2006 - International Plant Genetic Resources Institute (2006)
As the year 2006 comes to an end, the Genetic Resources Policy Initiative (GRPI) project is also preparing to wind up its activities in the six pathfinder countries and two sub-regions. Phase I of the project began with a comprehensive Demand Analysis (DA) process where data regarding demand for capacity strengthening and research was collected and synthesized. This was followed by a stage of identifying gaps between those demands and existing information as well as training possibilities. Subsequent national policy research priorities were identified in each country and sub-region leading to the current Phase II stage of the project scheduled to end in 2007. One of the most significant events held within the last quarter of 2006 was the GRPI-Wide Phase II and International Steering Committee (ISC) meeting. The former brought together GRPI Task Force (TF) representatives from all GRPI pathfinder countries and sub-regions with an aim of sharing experiences and forging a way forward as the project approaches conclusion. The ISC meeting, an annual undertaking which provides strategic and operational guidance for the project, was held after the GRPI-Wide Phase II meeting. It was noted that overall implementation of Phase II activities has been on a steady course throughout this year. These activities, most of which began in the year 2005, also generated tremendous interest among stakeholders who attended the meetings with notable observations being been made in regard to sustainability and other related aspects of the project. In this edition of our newsletter, we will provide an overview of progress of these activities in an attempt to provide information on some of the substantial achievements in this last quarter. Our online information sharing initiatives and networking activities are also highlighted. Other significant developments that were not mentioned in the previous edition of our newsletter owing to the evolving nature of their tasks and which ultimately are intended to support longer term policy research objectives are also included. We hope that by addressing these developments, further opportunities for conducting policy research and providing leadership in the underrepresented genetic resources policy arena will be realised. We also hope that relevant stakeholders will adopt appropriate action plans in respect to specific policy priorities, goals and objectives accordingly. Finally, we acknowledge with thanks all contributions to this newsletter, especially from our stakeholders in various national programmes who shared the activities they carried out in the immediate past - and which gave us an in-depth insight into the current research course. The purpose of this newsletter is to inform all our national partners and stakeholders of activities and events that are taking place in the Project. The unique design allows for quick and easy access to articles of interest to you. New articles will be added every time we produce the newsletter. There will be three editions of this newsletter for the purpose of targeting information that is relevant to your needs. For more information, do not hesitate to contact us. As always, we would like to extend our gratitude to all national partners and stakeholders who have played an instrumental role in our efforts aimed at strengthening capacity to analyse national options.